When Hollywood movies steal the show, stock returns dance more with the market! - Do HX; Nguyen NH; Nguyen QMP; Nguyen TVH; Truong C (Elsevier Inc, 2024)
Hollywood film releases attract U.S. investors' attention away from the financial markets. This is reflected in lower trading activity and abnormal Google search volume for firm names between film and non-film days. The resultant investor inattention leads to a significantly higher stock return comovement with the market on film release days. Interestingly, films with A-list star actors and blockbuster movies exhibit a more pronounced impact than their counterparts. Finally, we show that being aware of this Hollywood film-induced mispricing can yield an annualized abnormal risk-adjusted return of up to 13.5% within five days around the release events.
Keywords: Investor attention; Return Comovement; Hollywood; Entertainment industry